A DFT mechanistic study of the organocatalytic asymmetric reaction of aldehydes and homophthalic anhydride - ROZAS, ISABEL; CONNON, STEPHEN; Trujillo, Cristina; Botte, Astrid (My University, 2017)
The first DFT study of the cycloaddition of benzaldehyde with homophthalic anhydride under the influence of a bifunctional organocatalyst is reported. The catalyst first binds and then deprotonates the anhydride, leading to a squaramide-bound enolate, which then adds to the aldehyde with activation of the electrophile by the catalyst's ammonium ion.
Keywords: DFT; Benzaldehyde; Homophthalic anhydride